Perancangan Game Ular Tangga Untuk Edukasi Diklatsar Sispala Di Man 10 Jombang Berbasis Android - Ziana Zain Mohammad; Budiman Budiman; Winarti Winarti (Politeknik Kampar, 2023)
Technological developments have entered the world of education. Starting from the educational administration process to entering the delivery of learning materials in intracurricular and extracurricular activities. Entering the independent curriculum, extracurricular activities are activities that must be applied in schools, one of which is nature lovers activities at the high school level, namely SISPALA. At MAN 10 Jombang School, we have just established a student organization of nature lovers, which runs in the 2nd year so that students are minimal about nature-loving material. In delivering material in the form of an educational game carried out through electronic media, Android is an option because it is currently a communication tool that cannot be separated from teenagers and has an impact on changes in the game world, especially for online game activists. Like the snakes and ladders game, which has been played with board game media and equipped with a set of dice can be played by two or more players. The research method used in this study is the System Development Life Cycle Waterfall method is a method for software development. The sequence in the Waterfall Method is serial which starts from the process of planning, analyzing, designing, and implementing the system with a structured process using use case diagrams and Construct 2 as the software used. With the application that has been built later, it is expected to be able to provide benefits for users in adding material knowledge as a provision for mountain climbing.